PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 163 PEKANBARU - Rusdiani, Yulia; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low learning outcomes of the VA students at SD Negeri 163 Pekanbaru. It can be seen from learning outcomes results with an average score of 65,37 when the success criteria is 73. In order to solve this problem, the researcher decided to apply the Contextual Teaching and Learning (CTL) Model to the students. This research is Classroom Action Research (CAR), which consists of two cycles. Cycle 1 consists of two twice learning and one daily exam at the end of every cycle. Data collection techniques applied observation and evaluation while the technique of data analisysis applied qualitative and quantitative analysis. The subject of this research is the VA students of SD Negeri 163 Pekanbaru which contains of 41 students, consisting of 20 males and 21 females. Before the CTL model was applied, the teachers activity in Cycle I improved from 75% (enough category), to 81,25% (good category), and then it improved again in Cycle II improved from 87,5% (very good category) and became 93,75% (very good category). The students learning outcomes improved from 65,37 to 76,22 in daily exam I and it improved again in daily exam II becoming 86,46. With the implementation of Contextual Teaching and Learning (CTL) model, the students learning outcomes improve by 32,26%, therefore it can be concluded that the implementation of the Contextual Teaching and Learning (CTL) model can improve the learning social science learning outcomes grade students VA Negeri 163 PekanbaruKeywords: Contextual Teaching and Learning (CTL) Model, Social Studies Outcomes